Determination of reactive oxygen generated from natural medicines and their antibacterial activity - Noriko Tajima; Makiko Takasaki; Haruka Fukamachi; Takeshi Igarashi; Yoshijiro Nakajima; Hidetoshi Arakawa (Elsevier, 2016)
Extracts of 16 natural medicine powders (Galla chinensis, Malloti cortex, Cassiae semen, Sophorae radix, Myricae cortex, Crataegi fructus, Gambir, Mume fructus, Geranii herba, Phellodendri cortex, Coptidis rhizoma, Swertiae herba, and Cinnamomi cortex) were assayed for reactive oxygen concentrations using the peroxyoxalate chemiluminescent detection system. High luminescence intensity was observed in Galla chinensis, Geranii herba, Malloti cortex, Myricae cortex, and Cinnamomi cortex. Additional experiments identified the reactive oxygen species as hydrogen peroxide. Galla chinensis generated 2.4×10−4 mol/L hydrogen peroxide from a 1 mg/mL solution. In bacterial growth tests, Galla chinensis extract had antibacterial activity against Escherichia coli, Staphylococcus aureus, Bacteroides thetaiotaomicron, Campylobacter sputorum biovar sputorum, Streptococcus salivarius thermophilus, Lactobacillus casei, and Bifidobacterium longum infantis. This antibacterial activity was decreased by the addition of catalase. It revealed that hydrogen peroxide which Galla chinensis produced participated in antibacterial activity.